Amylase As An Early Serum Marker For Kidney Damage In Mild Hypertension -A Pilot Study - DR AMITA YADAV M.B.B.S, M.D.; DR RITU SINGH M.B.B.S, M.D. (International Journal of Pharma and Bio Sciences, 2010)
Mild hypertension is clinically asymptomatic but it is a risk factor for cardiovascular disease and cause progressive damage to kidney in long term. Hypertension has damaging impact of subclinical atherogenesis and glomeruli become dysfunctional and there is excretion of low molecular weight compound like albumin and amylase in urine. So the study was done to see the change in amylase levels in hypertension. It was a hospital based case control study involving 100 subjects. The patients were enrolled on the basis of history and clinical examination. The study was done in a tertiary care setup. The patients attending the medical opd were enrolled for study and samples were send in the clinical biochemistry lab. The study was conducted in 100 subjects consisting of 48 hypertensive patients and 52 normotensive subjects in age group 35-60 years. Serum samples were analysed for total protein, albumin and amylase Result: The study showed a statistically significant change in the levels of serum albumin and amylase. The level of serum albumin was 4.78± 0.39g/dl in case while it was 4.99± 0.49 g/dl in controls. The P value was 0.026 which was statistically significant. Amylase also showed statistically significant change in the values when controls were compared with cases. The serum levels were 129.60±39.72 mg/dl in control group while it was 112.06±30.70 mg/dl in the cases. The minimal damage to Glomerulus will be reflected in the change in serum amylase levels.